Accuracy of patient recall for self‐reported doctor visits: Is shorter recall better?. (2nd July 2018) - Dalziel, Kim; Li, Jinhu; Scott, Anthony; Clarke, Philip
Abstract: In health economics, the use of patient recall of health care utilisation information is common, including in national health surveys. However, the types and magnitude of measurement error that relate to different recall periods are not well understood. This study assessed the accuracy of recalled doctor visits over 2‐week, 3‐month, and 12‐month periods by comparing self‐report with routine administrative Australian Medicare data. Approximately 5, 000 patients enrolled in an Australian study were pseudo‐randomised using birth dates to report visits to a doctor over three separate recall periods. When comparing patient recall with visits recorded in administrative information from Medicare Australia, both bias and variance were minimised for the 12‐month recall period. This may reflect telescoping that occurs with shorter recall periods (participants pulling in important events that fall outside the period). Using shorter recall periods scaled to represent longer periods is likely to bias results. There were associations between recall error and patient characteristics. The impact of recall error is demonstrated with a cost‐effectiveness analysis using costs of doctor visits and a regression example predicting number of doctor visits. The findings have important implications for surveying health service utilisation for use in economic evaluation, econometric analyses, and routine national health surveys.